ANALISIS KARAKTERISTIK CURAH HUJAN DAN NERACA AIR LAHAN UNTUK PENETAPAN MUSIM TANAM DI HALMAHERA UTARA - Alfred Lodewyk Patty (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
This research has been conducted to analyze of the rainfall characteristics and water balanced were used to determination of growing periods in North Halmahera. The method was used is this research was a survey method in relation to data collection that were climate data which were taken from Gamar Malamo Meteorological Station at Galela, meanwhile soil, crops and land use data were taken from local agriculture office and other related institutions. To analyze of climate data several methods were used such as; ranking order method was used to analyze rainfall; modified Penman method to estimate potential evapotranspiration, bookkeeping system (way of Thorntwaite and Mather 1957 in Usman, 2004) to analyze water balance and Reddy method was used to determine available growing seasons. The results of climate data analyses entirely showed that the pattern of rainfall in north Halmahera is monsoon which characterized by one peak of rainfall occurred in May and also this area prevailing tropical seas climate with annually average rainfall is 2.300 mm. The length of available growing seasons in this area occurred for 8 – 12 months starting from November and ending in Oktober.